1980
DOI: 10.1037/0278-7393.6.4.391
|View full text |Cite
|
Sign up to set email alerts
|

The functional visual field during picture viewing.

Abstract: In four experiments, pictures of complex, naturalistic scenes were shown, followed by a two-alternative forced-choice recognition test in which the targets and distractors differed in only a single, critical detail. Eye movements were recorded at the time of study in the first two experiments. In Experiment 1 we investigated eye movements during short initial exposure times and found that if the nearest fixation to the critical detail was further than about 2° of visual angle, performance was no better than ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
105
2
2

Year Published

1985
1985
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(114 citation statements)
references
References 13 publications
5
105
2
2
Order By: Relevance
“…Although these data confirm that objects can be identified farther from fixation than words, two other lines of research suggest that there are limits to how far from fixation information can be extracted even in scene perception. First, Nelson and Loftus (1980) determined how close to fixation an object had to be for it to be recognized as being in the scene. They found that objects located within about 2.6 ° from fixation were generally recognized, but recognition depended to some extent on the characteristics of the object.…”
Section: How Important Are Eye Movements In Scene Perception?mentioning
confidence: 99%
“…Although these data confirm that objects can be identified farther from fixation than words, two other lines of research suggest that there are limits to how far from fixation information can be extracted even in scene perception. First, Nelson and Loftus (1980) determined how close to fixation an object had to be for it to be recognized as being in the scene. They found that objects located within about 2.6 ° from fixation were generally recognized, but recognition depended to some extent on the characteristics of the object.…”
Section: How Important Are Eye Movements In Scene Perception?mentioning
confidence: 99%
“…Appendix C Distance from Mentioned, but not Fixated, Objects Since the distance from a fixation is known to have processing implications (Nelson & Loftus, 1980), we performed an additional analysis in which we looked at the closest fixation to the referent when is not mentioned, and calculate the distance of this fixation from the object centroid. We find that on average, fixations are at 11.65 ± 5.04 degree of visual angle from the object centroid.…”
mentioning
confidence: 99%
“…A headrest was used to keep a distance of 50 cm between the participants' eyes and the screen. The target stimulus of both tasks-a circle 1.7 cm in diameter, corresponding with the foveal visual angle of 1-2', thus providing maximal visual acuity (Nelson & Loftus, 1980)-moved with a speed of 3 cm/s within a delineated area (18 X 24.5 cm2) on rhe screen in randomly designed curves.…”
Section: Procedures Equipment and Materialsmentioning
confidence: 99%